Assessment of growth performance of preruminant crossbred calves maintained on different feeding strategies - Dhanya Suresh; K. Ally; V. Dildeep; K. Jasmine Rani; K.S. Anil (Journal of Veterinary and Animal Sciences, 2023)
A study was conducted to assess the growth performance of pre-ruminant crossbred calves maintained on different feeding strategies. Eighteen four days old crossbred calves were selected from University Livestock Farm and Fodder Research and Development Scheme, Mannuthy. The calves were randomly allotted to three dietary treatments- T1 (fed with milk @ 1/10th of body weight during first six weeks, 1/15th of body weight during next two weeks, 1/20th of body weight during next four weeks), T2 (fed with milk at 15 per cent of body weight for first month and weaned at six weeks of age) and T3 (fed with milk replacer (22 per cent CP) at 15 per cent of body weight for first month and weaned at six weeks of age. Calf starter having 22 – 24 per cent CP and 70 per cent TDN was fed to T1 and one with 20 per cent CP and 70 per cent TDN) was fed to T2 and T3 as per standard feeding practices followed in the farm. Average daily gain and body weight gain were higher (p<0.05) in T2 compared to T3. However outcome of groups T2 and T1 and the comparison of the aforesaid parameters between T3 and T1 were similar. The fortnightly average daily dry matter intake of the calves did not differ between the various groups except for the fourth and fifth fortnight. The mean feed conversion ratio of experimental calves of T1, T2 and T3 were 3.46 ± 0.09, 3.11 ± 0.23 and 3.41± 0.19 respectively and the values were statistically similar (p>0.05).